Implementation of SADARI in the Early Detection of Breast Cancer in Young Women High School of West Aceh Regency - Husna, Arfah; Fahlevi, Muhammad Iqbal (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Breast cancer (carcinoma mammae) is a condition where cells have lost control and normal mechanisms, resulting in abnormal growth, rapid and uncontrolled which occurs in breast tissue.. Early detection of breast cancer aims to find cancer in the early stage so that the treatment is better. The detection is done by doing SADARI, SADARI is an easy examination to find a lump or agility others. The case of cancer of West Aceh Regency in 2015 S/d 2017 recorded the number of cases of breast cancer at most 24.43% compared with other cancers. Women aged 50 years more who have breast cancer reaches 52%, 35% at the age of less than 40 years, 22% of women aged 30 years and the younger age exposed to breast cancer is the age of 15 and 18 years. The study aims to determine the influence of breast cancer counseling and breast-check training (SADARI) in an effort to improve the knowledge and skills of young women in the Act of SADARI for prevention and decrease in cases of breast cancer. This research uses Quasi-Experimental design. The research plan is one group before and after intervention design, or one group pre and posttest design. The population in this study is young women SMAN District ACEH Barat with samples amounting to 30 young women. The results of the study concluded that there was an effect of BSE Implementation (counseling about breast cancer and breast self-examination training) in an effort to increase the knowledge of young women about breast cancer and the skills of young women in breast self-examination.